After Yang [videorecording (DVD)] - Farrell, Colin, 1976-; Turner-Smith, Jodie, 1986-; Min, Justin H.; Tjandrawidjaja, Malea Emma; Coster, Ritchie; Choudhury, Sarita; Collins, Clifton, Jr; Richardson, Haley Lu; Matsumiya, Aska; Weinstein, Alexander (Lionsgate, 2022)
When his young daughter's beloved companion, an android named Yang, malfunctions, Jake searches for a way to repair him. In the process, Jake discovers the life that has been passing in front of him, reconnecting with his wife and daughter across a distance he didn't know was there.